PENDAMPINGAN PENDIRIAN BMT DI KECAMATAN TEKARANG - Sumar’in Sumar’in; Nashirun Nashirun (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
In order to improve the quality of society in the financial sector, it is necessary to have Microfinance Institutions, which are considered to have a huge role in alleviating poverty. One type of microfinance institution is Baitul Maal Wat Tamwil (BMT) which implements the principles following Shari'ah. BMT is specifically regulated by the Decree of the State Minister for Cooperatives and Small and Medium Enterprises, namely No. 91/Kep/M.KUKM/IX/2004 concerning Guidelines for the Implementation of Sharia Financial Services Business Activities. From this decision, everything related to the establishment and supervision of BMT is under the Department of Cooperatives and Small and Medium Enterprises. The presence of BMT is very much needed in the community because most of the people, especially in Tekarang District, are predominantly Muslim who are engaged in micro-enterprises. The existence of this BMT is expected to contribute to economic development. BMT is a Sharia Microfinance Institution which is one of the alternatives in eradicating poverty. The problem in this PKM is how the efforts to establish the BMT Syariah Muamalah are in Kecanatan Tekarang and what products are produced from the establishment of the BMT. At the same time, the purpose of this PKM is to find out the extent to which efforts to assist the establishment of BMTs are established and to find out what products are produced after the establishment of BMTs in the Tekarang District. The results of this PKM are Based on the implementation of the PKM, which began withholding a seminar on the establishment of Baitul Maal Wat Tamwil on March 25, 2021, which was attended by religious and community leaders as well as from students, a temporary BMT board was formed, but after the second meeting on April 11, 2021, which took place in the Poltesa meeting room, could produce several points, namely, 1) the name of the BMT; BMT Syariah Muamalah 2) BMT Headquarters; Merubung Village, Tekarang District 3) the formation of the management structure of BMT Syariah Muamalah 4) the formation of the manager of BMT Sayariah Muamalah 5) the formation of BMT Syariah Muamalah products. The products produced from BMT Syariah Muamalah are murabahah products (buying and selling) and mudharabah products (profit sharing), with these two products starting the journey of forming BMT.